A formação de sentidos subjetivos potencializadores da amorosidade no espaço educacional - Solange Martins Oliveira Magalhães (EccoS – Revista Científica)
We live in times when subjects begin to be recognized as being paradoxical, in constant process of recreation. The understanding that everything connects to everything, conversely, a network of relationships and interdependence, has promoted the understanding that the individual is an autonomous being, but at the same time dependent on each other lovingly, a roundness that distinguishes and differentiates simultaneously. The weaving of a subject from this perspective involves articulating different threads of a process of humanization that pass through the formation of subjective meanings that equate mainly the inseparability of the cognitive and affective. It goes through a state of learning intensificadamente cooperative, supportive and loving. As noted by Morin (2002), it is also necessary to develop a loving consciousness conceived as an important part of a heightened awareness that can help the participants (teacher and student) to self-organize themselves, becoming continuously stimulating the formation subjective meanings capable of enhancing the educational space in lovingness and understanding of the real world. This way of conceiving the subject as one who can feel with reflection embodies the vision of complexity advocated by Morin (2001), considering the joints, interconnections, links, substantiating what is woven together.